Consistency and Momentum in NASCAR. (August 2017) - Depken, Craig A.; Hood, Matthew; King, Ernest
Conventional wisdom in sports is that consistency is praiseworthy and that competitors should seek momentum. A small standard deviation is the simplest measure of consistency, and a positive autocorrelation is the simplest measure of momentum. With these statistical definitions, we find that consistency is predictable for Sprint Cup drivers, but momentum is not. Simulating seasons, we find consistency reduces the variability in season-ending performances and momentum increases them. Since drivers are ordinarily seeking unlikely occurrences, consistency is harmful and momentum is beneficial. Thus, consistency is obtainable but not desirable, and momentum is desirable but not obtainable in National Association for Stock Car Auto Racing.